Distributed Construction of Connected Dominating Sets Optimized by Minimum-Weight Spanning Tree in Wireless Ad-Hoc Sensor Networks - Sijun Ren; Ping Yi; Dapeng Hong; Yue Wu; Ting Zhu (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
A Connected Dominating Set (CDS) is a subset V' of V for the graph G(V,E) and induces a connected subgraph, such that each node in V -V' is at least adjacent to one node in V'. CDSs have been proposed to formulate virtual backbones in wireless ad-hoc sensor networks to design routing protocols for alleviating the serious broadcast storms problem. It is not easy to construct the Minimum Connected Dominating Set (MCDS) due to the NP-hard nature of the problem. In this paper, our algorithm first finds a prior CDS and then uses the Minimum-Weight Spanning Tree (MST) to optimize the result. Our algorithm applies effective degree, the new term introduced in our algorithm, combining with ID to determine dominators. Default event is triggered to recalculate and update the node's effective degree after a predetermined amount of time. By 3-hop message relay, each node can learn the paths leading to the other dominators within 3-hop distance and thus some paths picked up by some rules can convert into the new weight edge by calculating the number of nodes over these paths. An MST will be found from the new weight graph induced by the prior CDS to further reduce CDS size. Our algorithm performs well in terms of CDS size and Average Hop Distance (AHD) by comparing with the existing algorithms. The simulation result also shows that our algorithm is more energy efficient than others.